2012
DOI: 10.1177/0194599811434889
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Incision Intraoral Silicone Chin Augmentation

Abstract: Based on our series, the intraoral technique with a midline incision avoiding disruption of the mentalis muscle is recommended for its ease, simplicity, patient satisfaction, low complication rate, and circumvention of an external scar. The external approach should be considered in cases that require a very large implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
0
31
0
6
Order By: Relevance
“…Solide siliconen zijn eenvoudig aan te passen aan de gewenste vorm. Omdat het materiaal buigbaar is, kunnen solide siliconen via kleine incisies worden aangebracht (Vuyck, 1996;Aynehchi et al, 2012). Aangebrachte solide siliconen passen zich gemakkelijk aan de vorm van de onderliggende benige structuur (Narsete et al, 2011).…”
Section: Siliconenunclassified
“…Solide siliconen zijn eenvoudig aan te passen aan de gewenste vorm. Omdat het materiaal buigbaar is, kunnen solide siliconen via kleine incisies worden aangebracht (Vuyck, 1996;Aynehchi et al, 2012). Aangebrachte solide siliconen passen zich gemakkelijk aan de vorm van de onderliggende benige structuur (Narsete et al, 2011).…”
Section: Siliconenunclassified
“…A recent investigation by Aynehchi et al [8] demonstrated efficacy in chin augmentation using a vertical intraoral approach among a series of 105 patients. This approach preserves the attachment of the mentalis muscle while achieving augmentation results and complication rates equivalent to other approaches [8]. Irrespective of the chosen surgical approach, a tightly dissected tissue pocket is critical in ensuring implant fixation.…”
Section: Mandibular Augmentationmentioning
confidence: 99%
“…yet its clinical consequences have yet to be determined [8]. Surgical principles dictate that an immobile implant is less likely to cause bone resorption, but this has yet to be empirically evaluated in the literature.…”
Section: Key Pointsmentioning
confidence: 99%
“…Padrões culturais e de gênero associam o mento mais protruído a caracterís-ticas de personalidade como força e confiança, enquanto um posicionamento retruso é associado à fragilidade (AYNEHCHI et al, 2012). Visando a mudança do perfil do mento o primeiro implante facial de silicone foi instalado no ano de 1953 (GOLDSMITH; HOROWITZ; ORENTLICHER, 2012), e desde então vem sendo amplamente empregado em mentoplastias, rinoplastias, cirurgias para projeção malar e frontal (SCHATZ; GINAT, 2012).…”
Section: Introductionunclassified